Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.3109/02713689409025135
|View full text |Cite
|
Sign up to set email alerts
|

Expression of keratins K12, K4 and K14 during development of ocular surface epithelium

Abstract: The 55 kDa keratin K12 and the 59 kDa keratin K4 were used as biochemical markers of differentiated corneal and conjunctival epithelium, respectively, to follow the temporal and spatial appearance of these cell types during embryonic development of the mouse eye. K12 was first detected in corneal epithelial cells of day 15 mouse embryos in a small subpopulation of superficial cells. At later developmental stages only suprabasal corneal epithelium expressed K12, however, in post-natal and adult cornea all cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 24 publications
6
80
0
Order By: Relevance
“…Thus, the expression of K12 mRNA and protein using three independent means of detection indicate that these cells retain features that are characteristic of corneal epithelial cells. K12 staining was not detected in corneas with reductions in corneal epithelial thickness to one or two cell layers; instead, these cell layers were positive for keratin 4 (K4), a conjunctival epithelium-specific keratin (Kurpakus et al, 1994) (data not shown). Thicker epithelia were negative for K4 staining (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the expression of K12 mRNA and protein using three independent means of detection indicate that these cells retain features that are characteristic of corneal epithelial cells. K12 staining was not detected in corneas with reductions in corneal epithelial thickness to one or two cell layers; instead, these cell layers were positive for keratin 4 (K4), a conjunctival epithelium-specific keratin (Kurpakus et al, 1994) (data not shown). Thicker epithelia were negative for K4 staining (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…For example, limbal SCs have the smallest cell size [5], are slow-cycling and hence label-retaining [6], and do not express markers destined for terminal differentiation such as cytokeratins 3 [1] and 12 [7][8][9], involucrin [10], and connexin 43 [11]. In contrast, the SC-containing limbal epithelium has a high proliferative potential in different cultures [12][13][14][15], and their in vitro proliferation is resistant to the inhibition by tumor-promoting phorbol esters [13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Initial differentiation in the epidermis is associated with a switch of cytokeratin expression from the universal stratified epithelial cytokeratin pair, K5 and K14, to K1 and K10, the tissue specific cytokeratins (TSCKs) of the skin (Moll et al, 1983;Cooper et al, 1985;O'Guin et al, 1987). Similarly, in the ocular surface epithelia there is an equivalent cytokeratin switch from the K5/K14 cytokeratins to their TSCKs, K3 and K12 (Schermer et al, 1986), and K4 (Kurpakus et al, 1994) for the cornea and conjunctiva, respectively. The main phenotypic differences with the epidermis occur in the late differentiation stages.…”
Section: Ocular Surface Epithelial Phenotypesmentioning
confidence: 99%
“…In the rabbit cornea, ChaloinDufau et al, (1990) detected the initial expression of K12 and K3 on embryonic (E) days 17 and 21, respectively. In mouse, where only K12 is expressed, Kurpakus et al, (1994) identified initial expression of TSCKs on the corneal zone on E15; K4 was initially expressed on E14 on the conjunctival zone overlying the lid bud (Pei and Rodin, 1970). An intriguing question that has not yet been addressed is whether expression of the universal type cytokeratins K5/K14 precedes the de novo appearance of the TSCKs.…”
Section: Developmental Expression Of Ocular Surface Epithelial Genesmentioning
confidence: 99%